PMU-based two stages state estimation for power system with nonlinear devices - Rakpenthai C. (2014)
This paper presents a two-stage state estimation method for power system containing multiple nonlinear devices. In this work two types of nonlinear devices are considered, phase-shifting transformers and unified power flow controllers. It is assumed that Phasor Measurement Units are available in order to obtain the required synchronized measurement values. The problem of state estimation is decomposed into linear and nonlinear sub-problems. First the bus voltages are estimated using measured data from the power network. Then these voltages and other measured data are used to estimate the nonlinear devices' states. The modified IEEE 14 bus test system is employed to demonstrate the effective of the proposed approach. © 2007 RPS.